Clinico-Pathological Evaluation of Oral Leukoplakia at Urban Sindh (Medical Forum Monthly, 2024)
Objective: To determine clinicopathological patterns of oral leukoplakia lesions in patients presenting at tertiary care hospitals of Rural Sindh.Study Design: Descriptive / cross-sectional studyPlace and Duration of Study: This study was conducted at the Dental Departments at Tertiary Care Hospitals in Urban Sindh from January 2016 to December 2016.Materials and Methods: One hundred and twenty patients having suspicious oral leukoplakia belonging to both gender and age between 20-70 years were included in the study. All the cases below 20 and above 70 years of age and having oral lesions that were not classified as leukoplakia were excluded. After initial thorough oral examination, an incisional and excisional biopsy of selected patients was carried out under local anesthesia. The oral tissues were processed with H & E staining which was then examined for histopathological changes by microscopy.Results: The most common age group (40%) was 31-40 years. Males were found in the majority (85%) as compare to female (15%). Majority (38.3%) patients were found to have more than one addictive chewing habits following by Smoking, Paan, Gutka, betel nut and Mainpuri which were found in percentages of 20.0%, 15.0%, 06.7%, 10.0% and 10.0%respectively. Most of the patients (56.7%) had lesion in buccal mucosa. Majority of the cases (76.7%) were found with homogenous leukoplakia. According to histopathological examination, almost all cases had mild and moderate dysplasia with percentage of 53.3% and 31.7% respectively. Hyperkeratosis without dysplasia was found in 8.3% patients, while only one case was found with severe dysplasia. A significant association was found between homogenous leukoplakia and mild and moderate dysplasia (p-value 0.001).Conclusion: The study concluded that young males were more affected by oral leukoplakia. Homogenous leukoplakia was the most common finding on clinical examination whereasmild and moderate dysplasia was found to be common on histopathology and the clinical type of leukoplakia correlates with the severity of dysplasia which increases the risk of malignancy in this population